Preferensi dan Kesediaan Membayar Konsumen Terhadap Kantong Belanja Ramah Lingkungan di Provinsi DKI Jakarta - Nur Oktavia Benedicta; Ahyahudin Sodri; Ninasapti Triaswati (School of Postgraduate Studies, Diponegoro Univer, 2024)
As a form of commitment to reducing the amount of plastic waste in the environment, DKI Jakarta Province has issued Governor Regulation Number 142 of 2019 concerning the Obligation to Use Environmentally Friendly Shopping Bags in Shopping Centers, Supermarkets and People's Markets. On the roadmap proposed by the United Nations Environment Agency, Governments developing policies will need to verify the existence of valid alternatives before banning plastic bags. However, in this regulation, the type, size, material, price and sales of eco-friendly shopping bags are the responsibility of the business actor. The definition of a reasonable price, type, size, and material of shopping bags provided by business actors in this regulation is not clear and can lead to different perceptions, causing the implementation of this regulation to be ineffective. In this study, the types and price limits of eco-friendly shopping bags were analyzed based on the perception and willingness of the public as consumers to facilitate the implementation of regulations related to the use of eco-friendly shopping bags, especially in DKI Jakarta Province. This study uses a qualitative approach by conducting a survey of 406 female respondents with an age range of 18-40 years who live in DKI Jakarta Province. Conjoint analysis is used to determine preferences for eco-friendly shopping bags using SPSS version 24. Consumers' willingness to pay for eco-friendly shopping bags is analyzed using the Contingent Valuation Methode (CVM) approach. Based on the research results, consumers prefer eco-friendly shopping bags that are made of cloth, can be reused, and prefer to bring or provide them themselves rather than being provided by businesses but paying a fee. According to consumers, material attributes are the most important, followed by environmental and economic attributes. If required to pay, 28% of respondents are willing to pay with higher price than the average estimated price of consumers' willingness to pay (WTP), which is IDR 2,380 a piece. The government can use the results of an analysis of people's preferences and willingness to formulate the policies.